Endependence: renewable energy in a rural community - Schuette, Krystal M. (Kansas State University, 2011)
Rural Kansas communities are almost entirely dependent on large energy corporations. These corporations, in turn, are almost completely dependent on fossil fuels for energy production. Three major implications exist within these dependencies: 1) the dependence of rural communities on large corporations reduces the potential of a local economy to support itself; 2) the dependence on fossil fuels has severe environmental impacts; and 3) fossil fuels are non-renewable resources and will inevitably be exhausted. A rural Kansas community has resources necessary to achieve and maintain energy independence in a renewable manner. The design of these systems in regard to economy, society, aesthetics, technology, and ecology will play a key role in sustaining these resources into the future. The intent of the project is to create a tool for rural communities to evaluate localized renewable energy potential using Washington, Kansas as an example. Several questions were addressed to determine the capacity and feasibility of each local energy resource: What renewable energy resources are available to a rural Kansas community and are they sufficient for the community to achieve energy independence? How can the resource or its production be designed and maintained in regard to its environmental impact and long-term viability? What are the implications of energy independence for the community’s identity? Because each question is dependent upon the answer to a previous question, a decision tree was the most viable method for the project’s analysis and development. Research into the technology and science associated with each resource provided a general knowledge of the definitions associated with and processes necessary to determine the feasibility of the resource. For resources receiving a positive feasibility rating, analysis continued with a basic cost/benefit analysis that compares potential costs involving implementation and maintenance with the payback, offsets, and incentives involved in utilizing each resource. Analysis of each feasible resource continued with site suitability analysis. The analysis of each resource resulted in resource maps showing potential implementation locations for three renewable resources studied: hydro, wind, and solar. The maps and accompanying graphics communicate the integration of renewable energy technologies into the existing community’s identity.
Independence: renewable energy in a rural community
Keywords: Renewable energy resources; rural communities; rural energy; micro-generation; rural power; energy independence; Alternative Energy (0363); Landscape Architecture (0390)